Pemberian kecambah kacang kedelai terhadap kadar malondialdehid (MDA) dan superoxide dismutase (SOD) tikus Sprague Dawley hiperkolesterolemia - Denny Indra Setiawan; Kusmiyati Tjahyono; Diana Nur Afifah (Jurnal Gizi Klinik Indonesia, 2016)
Background: Consumption of foods high in fat that happens in society can cause free radicals and trigger oxidative stress that results in the accumulation of fat cells in the adipose, cells damage and even cells death. An antioxidant activity that originates from food in the body, depends on the number of substances that can be absorbed and used to metabolism process. The selection of groceries that right can be alternatives management in hyperlipidemia. Soybean sprouts have properties that neutralize free radicals cause hyperlipidemia and cardiovascular diseases because it is an antioxidant compound. Objective: The aim of this study was to determine the effect of soybean sprouts (Glycine Max) to levels of MDA and levels of SOD of male Sprague-Dawley rats. Method: Research laboratory tests design post only controlled group design. The sample was 30 tailed rat Rattus norvegicus species Sprague Dawley. The rat 8-10 weeks and samples to be divided into 5 group. Group 1 was normal rat without treatment; groups II are hypercholesterolemic rat without treatment; groups III are hypercholesterolemic rat with treatment sprouts soybeans 0,53 g; group IV are hypercholesterolemic rat with treatment sprouts soybeans 1,06 g; the group V are hypercholesterolemic rat with treatment sprouts soybeans 2,12 g and all groups are treatment for 4 week. Results: After four weeks of treatment, decline MDA levels in the hypercholesterolemic rat. Doses the provision of sprouts soybean 2,12 g/day is dosed most effective shown the significant differences (p<0.05) between the treatment group first to the treatment third group. Statistical analysis to SOD levels show differences meaningful in all the treatment group (p<0.05). Doses the provision of sprouts soybean 2,12 g/day proven effective against elevated levels of sod who demonstrated the significant differences (p=0,004) between the treatment group 1 (X1) to the treatment group 3 (X3). Conclusion: Doses sprouts 2,12 g is dosed optimal in preventing elevated levels of MDA and help improve levels of SOD hypercholesterolemic Sprague-Dawley rats.